Formalizing the Survivability Target Function of Information System on Mobile Platform - Рубан, І. В.; Ткачов, В. М. (ХНУРЕ, 2025)
The purpose of the work is to formalize the survivability target function of an information system based on a mobile platform for selecting information system operating policies under disturbances. A multi-level model of an information system on a mobile platform is considered, which includes SLO requirements and causal-temporal consistency invariants. The target function combines the mean service shortfall, the CVaR tail risk measure, the penalty for approaching the survivability region, and the cost of reconfigurations, making it suitable for minimization on a sliding horizon under partial observability. Simulations with intermittent channels show a reduction in tail losses and time spent outside the acceptable region at moderate resource costs. The approach provides a consistent trade-off between risk, safety, as well as resources and serves as a single operational criterion for real-time survivability management.
Keywords: information system; survivability; target function; mobile platform; survivability core; partial observability